Pengaruh Current Ratio dan Debt To Assets Ratio Terhadap Pertumbuhan Laba Pada PT. Indofood Sukses Makmur - Angelle Liany Riyanto (STIKes Ibnu Sina Ajibarang, 2023)
A manufacturer of various types of food and beverages in Jakarta, Indonesia named PT. Indofood Sukses Makmur Tbk. This company was founded as PT. Panganjaya Intikusuma on August 14, 1990, and changed its name to Indofood Sukses Makmur on February 5, 1994. The purpose of this study was to determine whether the Current Ratio, Debt to Asset Ratio has an effect on Profit Growth either partially or simultaneously at PT. Indofood Success Prosperous. The population and sample of this research are PT. Indofood Sukses Makmur period 2016-2022. The method used in this research is statistical quantitative and the technique used is purposive sampling. The variables used in this study are the current ratio (X1), debt to asset ratio (X2), and profit growth (Y). The results of the study show that the current ratio variable has a negative effect on profit growth and the debt to asset ratio variable has no effect on profit growth.